Three Melodramas - Hughes, Ed (BFI, 2012)
The BFI presents three films by Japanese director Yasujiro Ozu. Melodrama is not a word usually associated with Ozu's quietly poetic oeuvre but his post-war "Early Spring" (1956) and "Tokyo Twilight" (1957) combine darker elements with his idiosyncratic style to create powerful dramas. [www.bfi.org.uk]
Keywords: DVD-Video